PENGARUH KOMITMEN MANAJEMEN PUNCAK DAN PERAN AKUNTAN MANAJEMEN TERHADAP SISTEM INFORMASI LINGKUNGAN DAN DAMPAKNYA KEPADA KINERJA LINGKUNGAN - Toto Kurniawan; Ririn Breliastiti (Jurnal Akuntansi Bisnis, 2017)
Disclosure of information about environmental performance (environmental performance information) to external parties is an important step to show that the company is a good corporate citizenship. Top management realized that the commitment on environmental sustainability can provide a competitive advantage to companies through reduced costs, increased market share, image enhancement and technological leadership. In addition, the role of the management accountant had already increasingly taken into account. The seriousness of top management and company management accountants will be reflected in the establishment of an information system in which to accommodate information about the environment. In practice, most companies do not have adequate systems for measuring and managing environmental costs, or coordinate the collection of environmental data for managerial decisions. This study aims to determine the effect of directly or indirectly from the top management commitment and the role of the management accountant which is mediated by the information system environment on environmental performance. The population in this study are private companies that are domiciled or headquartered in Jakarta. The method of selecting samples using a convenience sampling and purposive sampling. Respondents who have been targeted in this research is the employee who has occupied the minimum level supervisor. The data used are primary data collected through questionnaires. Data analysis was performed using analysis of PLS (Partial Least Squares). The results showed that the top management commitment, both directly and indirectly affect the environmental performance. The role of the management accountant directly affect environmental performance. Environmental information system influence on environmental performance.Keywords: top management commitment, the role of management accountants, environmental information systems, environmental performance, management accounting